Mechanisms of apoptosis from structural biology - Shi, Yigong (Henry Stewart Talks, 2007)
Structural mechanism of IAP recognition by Smac/DIABLO, Structural mechanism of caspase-9 inhibition by XIAP-BIR3, Structural mechanism of effector caspase inhibition by XIAP, Structural mechanism of initiator caspase activation, Structural biology of the apoptosome, Structural biology of the programmed cell death pathway in C. elegans